Employee Responses to Changing Aspects of the Employer Brand Following a Multinational Acquisition: A Longitudinal Study. Issue 1 (24th January 2013) - Edwards, Martin R.; Edwards, Tony
Abstract This study examines changing employment brands in the context of a multinational acquisition, specifically the implications for current employees. Using a sample (N = 251) from both the acquired and acquiring workforces, employees are tracked across 12 months following acquisition. The study explores predictors of identification with the acquiring organization, intent to quit, and discretionary effort. We focus on employment brand–related predictors, specifically perceptions linked to the provision of unique employment experiences, organizational identity strength, perceived prestige, and judgments of whether the acquiring organization acts in accordance with its corporate identity claims. The study showed that perceptions of prestige immediately after acquisition predict identification 12 months hence, as do judgments of whether the organization acts in accordance with its corporate social responsibility–based corporate identity claims. These judgments also predict subsequent levels of discretionary effort and long‐term intent to leave, as do perceptions linked to the provision of unique employment experiences. Perceived change in these unique employment experiences is also related to change in identification and intent to leave across time. Importantly, these elements have a varied effect on the adjustment outcomes when comparing the two workforces.